Characterizing College Students Who Self-Identify as Consuming Plant-Based or Animal-Based Diets: A Pilot Study. (29th May 2020) - Lachapelle, Rachel; Piccolo, Francesca; Melanson, Kathleen
Abstract: Objectives: College students often make their own diet choices for the first time in their lives. Growing trends are seen for self-reported plant-based (PB) and animal-based (AB) diets in this population. Little is known about how college students perceive PB versus AB diets. Knowing this may be important for diet education in this population, and for designing research. Methods: Thirty college students (23 females; 20.5 ± 2.76 years; BMI 25.8 ± 5.8 kg/m 2 ) were recruited for this cross-sectional study of PB vs AB diets, with 15 self-identifying as consuming each diet. Prior to the single lab visit, participants completed an online demographic and dietary screening questionnaire with questions on weekly servings of red meat, poultry, fish & shellfish, eggs, and dairy. On test days, fasting measures were taken of height, weight, and body composition by multi-frequency segmental bioimpedance (InBody 770). Independent t-tests compared students self-identifying as AB vs. PB with respect to food groups, BMI, body fat, and lean body mass. Data are expressed as means ± standard deviations. Results: Of the 15 students self-identifying as eating a PB diet, 87% were female, whereas in AB 67% were female. No significant differences were seen between AB and PB groups in any body composition variable (p > 0.05). Students in PB reported fewer weekly servings than AB of red meat (0.0 ± 0.0 vs 2.1 ± 1.1; P = 0.000), poultry (0.0 ± 0.0 vs 5.2 ± 2.3; P = 0.000), fish & shellfish (1.3 ± 2.2 vs 2.7 ± 0.84; P = 0.024), and dairy (3.0 ± 3.0 vs 6.4 ± 2.7; P = 0.003). Egg servings did not differ significantly between PB and AB (2.4 ± 2.7 vs 3.5 ± 2.0; P = 0.221). Two students in PB reported no servings from any animal foods category. Two students from AB reported >30 servings of animal foods weekly (30.5 & 37). Overall, the PB group reported fewer ( P = 0.000) total animal food servings weekly (9.3 ± 6.5) than AB (23.4 ± 5.3). Conclusions: In this pilot study, students self-identifying as eating PB versus AB diets did not differ in body composition, but they ate varying degrees of animal foods. On average, students in the PB group reported consuming 1.3 animal food servings daily compared to 3.3 daily in the AB group. More work is needed with larger samples, but this data provides insights for diet counseling and research planning. Funding Sources: This COMPACT study was funded by The University of Rhode Island Undergraduate Research Initiative Fund.